PEMIDANAAN TERHADAP PELAKU YANG MENDISTRIBUSIKAN GAMBAR PORNOGRAFI: Punishment Of Offenders Who Distribute Pornographic Images - Nida Zhakia Jasmine; Andi Widiatno (Reformasi Hukum Trisakti, 2024)
Decision Number 812/Pid.sus/2021/PN Bjm states that the criminal act of distributing pornographic images, which is regulated in Article 27 paragraph (1) UU ITE Law, is the lex specialist of the Criminal Code because it regulates the dissemination of information through Internet. The formulation of the problem in the decision is pornographic images are included in the moral content of Article 27 paragraph 1 of the ITE Law pornographic images with Article 45 paragraph 1 in conjunction with Article 27 paragraph 1. To answer this problem the research method used is Normative law using secondary data from primary and secondary legal materials accompanied by analytical descriptive research and discussion and research results pornographic images are considered to be moral in Article 27 paragraph 1 of the ITE Law. However, there was a discrepancy in the sentence imposed on the defendant. Even though a prison sentence of 3 years was required, the decision gave a sentence of 2 years, not considering the fact that defendant also committed the crime of creating and manipulating electronic information before distributing pornographic images. The conclusion from this research is that defendant should be sentenced under Article 35 in conjunction with Article 51 of the ITE Law.